Sistem Informasi Manajemen Data Pasien Untuk Meningkatkan Pelayanan Kesehatan Di Puskesmas Curug - Isnaeni Siktin Kusuma Desi; Syarifuddin (LPPM STMIK ANTAR BANGSA, 2019)
Abstract— The quality of service in health services is very important to be considered, because the importance of service quality is to meet the needs and desires of patients, which can produce patient confidence which is an indicator of the success of the delivery of health services. While the use of technology is also very important as a means of increasing patient care. In the Technical Implementation Unit (UPT) of Curug Puskesmas, there are obstacles due to the recording of patient data that starts from the registration process until the preparation of patient registration reports is done by recording and there are piles of paper stored on storage shelves, so that errors often occur and when parties puskesmas need patient data, it takes a long time to find where the data is stored. Another problem arises when many patients come for treatment and have to queue to fill out the registration form or the patient visit form. So we need a computerized system and a system that can provide information about UPT. Puskesmas Curug to patients or the general public online.